The use of the genetic algorithm to match English character patterns - Maha Al-Badrani (College of Education for Pure Sciences, 2007)
ABSTRACT The focus of the present research is on the issue of compatibility of the patterns of the English letter through the use of a probable research Algorithm called the Genetic Algorithm. The research clarifies the ability of the algorithm in the compatibility of patterns between the original(ideal) pattern of the letter and the deformed patterns since the genetic algorithm is good for some tasks that require examples. It applies to the issues that have large (wide)areas and large variables. It can also be easily in addition quickly solved, in addition to that ,it provides a solution that is quite near to the ideal solution of the patterns used. The results have proved the ability of the algorithm to carry out the process of the compatibility of the patterns of English Letters compared with other algorithms. الملخص ترکز الاهتمام فی هذا البحث على مسألة تطابق الأنماط للحرف الإنکلیزی باستخدام خوارزمیة بحث احتمالیة تدعى الخوارزمیة الجینیة. یوضح البحث إمکانیة الخوارزمیة فی تطابق الأنماط ما بین النمط الأصیل (المثالی) للحرف والأنماط المشوهة، لکون الخوارزمیة الجینیة جیدة لعدد من الأعمال التی تتطلب الأمثلة، فهی تطبق على المسائل التی تمتلک مساحة واسعة ومتغیرات کبیرة وفی الامکان حلها بسهولة وسرعة، کما إنها تعطی حلا قریباً جداً من الحل المثالی للأنماط المستخدمة. برهنت النتائج على قدرة الخوارزمیة على إجراء عملیة تطابق الأنماط للحروف الإنکلیزیة مقارنة بخوارزمیات أخرى .